2005
DOI: 10.1037/0278-7393.31.5.1105
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Between Judgments and Outcome-Expectancy Measures in Covariation Learning: A Signal Detection Theory Approach.

Abstract: A number of studies using trial-by-trial learning tasks have shown that judgments of covariation between a cue c and an outcome o deviate from normative metrics. Parameters based on trial-by-trial predictions were estimated from signal detection theory (SDT) in a standard causal learning task. Results showed that manipulations of P(c) when contingency (deltaP) was held constant did not affect participants' ability to predict the appearance of the outcome (d') but had a significant effect on response criterion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
103
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(116 citation statements)
references
References 35 publications
(58 reference statements)
10
103
2
1
Order By: Relevance
“…In contrast to this dominant view, a recent study by Ratcliff and Nosek (2010) obtained support for a dual-process performance interpretation quite similar to the one proposed by Allan et al (2005) and Perales et al (2005) in the area of contingency learning. Unlike previous experiments on illusory correlation, in the study conducted by Ratliff and Nosek (2010) participants had to report their explicit attitudes towards the majority and the minority groups, and their attitudes also were measured by means of an Implicit Association Test (IAT; Greenwald, McGhee, & Schwartz, 1998).…”
Section: Iat and Illusion Of Causalitymentioning
confidence: 57%
See 4 more Smart Citations
“…In contrast to this dominant view, a recent study by Ratcliff and Nosek (2010) obtained support for a dual-process performance interpretation quite similar to the one proposed by Allan et al (2005) and Perales et al (2005) in the area of contingency learning. Unlike previous experiments on illusory correlation, in the study conducted by Ratliff and Nosek (2010) participants had to report their explicit attitudes towards the majority and the minority groups, and their attitudes also were measured by means of an Implicit Association Test (IAT; Greenwald, McGhee, & Schwartz, 1998).…”
Section: Iat and Illusion Of Causalitymentioning
confidence: 57%
“…Although their theoretical interpretation of this finding is framed in different terms, it is surprisingly similar to the dual-process account provided by Allan et al (2005Allan et al ( , 2007 and Perales et al (2005) for cue-and outcome-density biases in contingency learning. In line with the popular dual-process framework proposed by Gawronski and Bodenhausen (2006), Ratliff and Nosek concluded that the fact that only explicit evaluations showed the illusory correlation effect suggests that the bias is not due to the way associations are encoded in memory (which is assumed to be indexed by the IAT), but to deliberate reasoning processes that qualify the expression of these associations (which is assumed to influence only explicit measures).…”
Section: Iat and Illusion Of Causalitymentioning
confidence: 70%
See 3 more Smart Citations